Análisis del marco regulatorio de empresas y derechos humanos frente al trabajo infantil en la cadena de valor global del algodón: caso de la industria algodonera en Perú - Perez Andrade, Yomeini (2024)
This research analyzes the regulatory framework for business and human rights in addressing child labor in the Peruvian cotton industry. It examines the global context of child labor in value chains, the evolution of international standards on business and human rights, and the relevant Peruvian regulatory framework. The study focuses on the practical implementation of these norms in the cotton sector, evaluating the adoption of international standards by companies, the effectiveness of state policies and programs, and monitoring and compliance mechanisms. Significant progress is identified in the formal adoption of international standards and the development of national policies. However, persistent challenges in effective implementation are revealed, including limitations in resources for labor inspection, gaps in coverage of rural areas, and the prevalence of informality in the sector. The research concludes that while the regulatory framework provides an important foundation, its effectiveness is limited by implementation challenges and the need to address the structural causes of child labor. Recommendations are proposed to strengthen the effectiveness of the regulatory framework, including improving monitoring mechanisms, strengthening interinstitutional coordination, and promoting more comprehensive approaches that address the root causes of child labor in the cotton sector.